Binder-free prickly nickel nanostructured/reduced graphene oxide composite: A highly efficient electrocatalyst for hydrogen evolution reaction in alkaline solutions. (1st August 2017) - Karimi Shervedani, Reza; Torabi, Mostafa; Yaghoobi, Fatemeh
Graphical abstract: Highlights: Efficient & binder - free prickly nickel nanostructured/graphene is made for electrocatalytic HER. Surface analysis showed that PNiNS wrapped in RGONs was pinned into Cu-Nifpl by prickles. Nanocomposite exposed excellent stability & electrocatalytic activity, b = 43 mV/dec, η20 = −57 mV. Increased activity comes partially from improved surface roughness & mainly synergetic effect . Abstract: Non-precious metal electrocatalysts with high activity towards hydrogen evolution reaction (HER) are desirable regarding renewable energy devices such as fuel cells and water electrolysis. However, fabrication of new materials for this purpose remains a main challenge. Here, a binder-free nanocomposite, prickly nickel nanostructured/reduced graphene oxide nanosheets, is constructed via electroless - deposition on cupper surface covered with a fresh prelayer of nickel (Cu-Nifpl -PNiNS/RGONs) for the first time. Then, the fabricated system is tested successfully for the HER in alkaline solutions. Structure and activity of the composite are characterized quantitatively by surface techniques and electrochemical methods. The results show that the hedgehog-like prickly nickel nanostructures wrapped in the RGONs cloth are formed, pinning the PNiNS/RGONs into the Cu-Nifpl surface, resulting in exceptional stability and activity for the Cu-Nifpl -PNiNS/RGONs system. In effect, the composite has shown excellent structural stability against disintegration by ultrasound waves; and electrocatalytic activity towards the HER as η20 = −57 mV, Tafel slope = −43 mV dec −1 and j0 = 1.05 mA cm −2, quite close to −22 mV, −40 mV dec −1 and 5.88 mA cm −2, obtained in the same conditions for commercial Pt/C, respectively. The remarkable increase in electrocatalytic activity was found to be originated partially from increase in the surface roughness and mainly from synergetic chemical coupling effects between PNiNS and RGONs.